New species of Neotropical Plecia Wiedemann (Diptera: Bibionidae) and delineation of the americana-, nigra-, and xyele- species-groups - Fitzgerald, Scott J. (Zootaxa, 2021)
Four new Neotropical species of Plecia Wiedemann (Diptera: Bibionidae) are described: P. abruptavena sp. n. (Colombia), P. elsalvadorensis sp. n. (El Salvador), P. nessiae sp. n. (Brazil), and P. schusteri sp. n. (Guatemala). Additionally, P. marginata Edwards is redescribed and the male described for the first time. A discussion of Neotropical species-groups is given and three species-groups based on male terminalia are outlined to include the new taxa: the americana-group (7 species), nigra-group (13 species), and xyele-group (2 species).